Strategies for Cost-Effective Supplementation of Beef Cattle - Matt Hersom; W. E. Kunkle (EDIS)
Forage should provide the majority of the nutrition for the beef herd. Seasonal forage growth and changes in forage quality challenge most cattle managers to provide adequate nutrition at reasonable costs. This revised 6-page fact sheet gives several alternatives to consider in your cow-calf production system. Written by Matt Hersom and W.E. Kunkle, and published by the UF Department of Animal Science, October 2011.